A Study of Knowledge of Vinayavinicchya in Bhikkhunivibhanga - Rachatatrirapinyow, Bupphachart; Thangthongmadan, Sathien (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 13 No 1 (2021): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
This thesis has three objectives: 1) to study the judgment of the discipline as shown in the Theravada Buddhist scriptures, 2) to study the judgment of the discipline as shown in the Bhikkhuni Viphang scriptures, and 3) to analyze the diagnosis of the discipline as shown in the scriptures. It is a documentary research. The research results were found that A monk when he was ordained into the diocese In Buddhism, we adhere to and abide by the Discipline, which is a scripture that has compiled the rules of conduct for the training of body, speech and mind that the Lord Buddha has laid the foundation of behavior in order to preserve the chastity sex, when giving this body to the holding of sex, the monk Vinai is like a representative of Lord Buddha. When his Highness Dabkhan Nirvana,The Vinaipitaka code of Buddhist commandments, which consists of regulations tradition The way of life and the way of conducting various activities of the monks in those days and have been practiced until now It can be regarded as like a monk's law. That has set the rules of imposing heavy punishments or moderately reduced Determination of the punishment for the offense committed Buddhist monks, even though they practice very well. Inevitably brings good results to the practitioner Resulting in peace and order to the monks The ruling of the discipline in the Bhikkhuni scriptures is divided into two groups: the public law and the law. In bhikkhuni, the phantom is public law. It is a sikyadet that only monks maintain, 130 Sikyadet and public commandments. Prescribed by monks to preserve and nuns should be treated as well. 181 Sikkhapada are structured and the essence of the monks is divided into seven kuns, consisting of the Senate Kan Sangkhathisakhan. Nissakiyakun Pachitthiyakan Discipleship of Tessanee Kan Sekhikhan and Akhon Samatha Judgment of the Discipline in Bhikkhuni Divided into 2 characteristics: 1) the general diagnosis has 17 items, such as objects, abuses, deeds, etc. 2) The diagnosis of each Sikkhapada consists of the Sikkhapada Wipang Act, etc. Considered a precepts to the nuns Must adhere to strict observance Leading to the mindfulness of the body. Verbal is like a form of a physical-verbal practice. According to the monk's discipline Inevitably it is for the beautiful body of speech which is the basis of which leads to the ultimate goal in Buddhism.